Silenciosas e silenciadas: descortinando as violências contra a mulher no cotidiano da prostituição em Natal-RN - Diniz, Maria Ilidiana (2009)
The prostitution is known as the world's oldest "profession", according to some historians, "the contemporary civilization itself." However, to refer it that way, we can systematically emptying it of expressions of violence that permeate. Furthermore, this statement tries to legitimize prostitution as a practical historically related to the natural condition of women. The main objective of the research is to examine how the activity prostitucional potentiates in different forms of violence in everyday development of prostitution in the city of Natal. Accordingly, the spot of the categories of gender relations and patriarchal violence against women, refute the thesis advocated by much of feminist studies on of prostitution as an expression of autonomy of women and overcoming the patriarchal order of gender. Procedures as set methodological quali-quantitative approach, guided by the method historicalmaterialist dialectic that allows us to apprehend the object of study beyond their immediate, unmasking its contradictions. We conducted nine interviews with prostitutes belonging to the classes of People who develop the activities in the streets and prostitutes Natals` cabarets. We hand with the systematic observation activities promoted by the Association of Prostitutes in Rio Grande do Norte ASPRORN, as the visits to cabarets, as well as participation in seminars held by this entity, at which establish contacts with informants-c which have facilitated access to interviewed. We note that the economic dimension is the factor determinant for their inclusion in prostitution, all to recognize as who found an alternative for survival, since most do not has no professional training and education. Another issue important to be emphasized concerns the areas where unhealthy develop programs which by itself is characterized as a denial of rights, expressed in the socioeconomic inequality that are subject. As the expressions of violence in their daily lives, the main forms identified were the physical and social, however, there is a trend in naturalizes them, the secondary-over other issues identified as most pressing, such as not service payment by the customers. The determinants of violence identified by respondents were assigned to the woman, or is its boldness. We also, the omission of the State in the issue of prostitution, mainly embodied in absence of public policies directed to sexual rights and reproductive and generation of employment and income. Regarding the regulation of prostitution, the majority of the interviewees is contrary, arguing that exacerbate the stigma in this practice